Nordic Regional Report : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
This Selected Issues paper elaborates findings and discussions of 2013 Cluster Consultation Nordic Regional report. The countries have close economic and financial ties and face some common challenges and shared risks, such as large banking sectors and high household debt. The economic performance of the four continental Nordic economies (Denmark, Finland, Norway, and Sweden-Nordic-4) ranks among the advanced economic development circle. It is analyzed that the large Nordic banking systems support relatively high levels of private sector debt. House price developments in the Nordic-4 pose a risk to broader macroeconomic stability in the context of strained household balance sheets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet